Lymph node biophysical remodeling is associated with melanoma lymphatic drainage. Issue 11 (15th July 2015) - Rohner, Nathan Andrew; McClain, Jacob; Tuell, Sara Lydia; Warner, Alex; Smith, Blair; Yun, Youngho; Mohan, Abhinav; Sushnitha, Manuela; Thomas, Susan Napier
ABSTRACT: Tissue remodeling is a characteristic of many solid tumor malignancies including melanoma. By virtue of tumor lymphatic transport, remodeling pathways active within the local tumor microenvironment have the potential to be operational within lymph nodes (LNs) draining the tumor interstitium. Here, we show that lymphatic drainage from murine B16 melanomas in syngeneic, immune‐competent C57B1/6 mice is associated with LN enlargement as well as nonuniform increases in bulk tissue elasticity and viscoelasticity, as measured by the response of whole LNs to compression. These remodeling responses, which quickly manifest in tumor‐draining lymph nodes (TDLNs) after tumor inoculation and before apparent metastasis, were accompanied by changes in matrix composition, including up to 3‐fold increases in the abundance of soluble collagen and hyaluronic acid. Intranodal pressures were also significantly increased in TDLNs (+1 cmH2 O) relative to both non‐tumor‐draining LNs (‐1 cmH2 O) and LNs from naive animals (‐1 to 2 cmH2 O). These data suggest that the reorganization of matrix structure, composition, and fluid microenvironment within LNs associated with tumor lymphatic drainage parallels remodeling seen in primary malignancies and has the potential to regulate the adhesion, proliferation, and signaling function of LN‐resident cells involved in directing melanoma disease progression.—Rohner, N. A., McClain, J., Tuell, S. L., Warner, A., Smith, B., Yun, Y., Mohan, A., Sushnitha, M., Thomas, S. N. Lymph node biophysical remodeling is associated with melanoma lymphatic drainage. FASEB J. 29, 4512‐4522 (2015). www.fasebj.org